Nanocellulose interface enhanced all-cellulose foam with controllable strength via a facile liquid phase exchange route. (1st January 2023) - Sun, Longfei; Liu, Lin; Wu, Mingbang; Wang, Dengfeng; Shen, Rongsheng; Zhao, Hanfei; Lu, Jing; Yao, Juming
Abstract: The development of sustainable, biodegradable, non-toxic biomass foams with outstanding physical properties to replace traditional petroleum-based foams is urgent. In this work, we proposed a simple, efficient, and scalable approach to fabricate nanocellulose (NC) interface enhanced all-cellulose foam through ethanol liquid phase exchange and subsequent ambient drying. In this process, NCs served as reinforcer and binder were integrated with pulp fiber to improve cellulose interfibrillar bonding and interface adhesion between NCs and pulp microfibrils. The resultant all-cellulose foam displayed stable microcellular structure (porosity of 91.7–94.5 %), low apparent density (0.08–0.12 g/cm 3 ), and high compression modulus (0.49–2.96 MPa) by regulating the content and size of NCs. Further, the strengthening mechanism of the structure and property of all-cellulose foam were investigated in detail. This proposed process enabled ambient drying, and is simple and feasible for low-cost, practicable, and scalable production of biodegradable, green bio-based foam without special apparatuses and other chemicals. Graphical abstract: In this work, a simple, efficient and scalable approach was developed to fabricate lightweight, robust and biodegradable all-cellulose foam without special apparatuses and other chemicals. The incorporation of NCs improved cellulose interfibrillar bonding and interface adhesion between NCs and pulp microfibrils, and promoted the formation of stable 3D network structure resisting the increased capillary force in the ambient drainage process. The resultant all-cellulose foam displayed stable microcellular structure, low apparent density, and high compression modulus. Unlabelled Image